Relationships between job satisfaction and organizational commitment towards turnover intention among medical officers in Hospital Ampang / Haryati Dollah and Nor Hafizah Abd Razak - Dollah, Haryati; Abd Razak, Nor Hafizah (2020)
The phenomenon of turnover is inevitable in any organization. This issue brings massive ramifications on cost to the organization especially during the training and recruiting process. It also gives negative perception from external stakeholder’s due impact of performance of that are influenced by the turnover. Job satisfaction and organizational commitment are two key constructs identified that influence the turnover intention. This study is conducted to examine the relationship between job satisfaction and organizational commitment towards turnover intention among medical officers in Hospital Ampang. For this study, non-probability sampling technique was used. A total of 175 respondents consisting of medical officers in Hospital Ampang participated in the study and the data that has been collected was analyzed using Statistical Package for Social Science (SPSS). Descriptive analysis presented the demographic profile of respondents. Research questions were answered using the Correlation Analysis and the SWOT tool to elucidate the eco-system surrounding the issue affecting turnover at Hospital Ampang. This research has found out that both job satisfaction and organizational commitment have negative relationships with turnover intention. Recommendation were provided using TOWS analysis according to findings in SWOT analysis.